Åkerböna i samodling med vårvete som helgrödesensilage till mjölkkor - Haag, Therese (2008)
The aim of this undergraduate thesis was to formulate advices regarding the use of field beans, cultivated together with spring wheat, as whole-crop silage in feeding to dairy cows. In the thesis, optimal harvest time of the field bean/spring wheat crop, as well as the feeding value and the fermentation quality, was studied. On the research station at Röbäcksdalen in Umeå field bean/spring wheat (70 % respective 30 % of normal seed rate for the pure crop) and pea/oat (70/30) was grown in field experiments both 2002 and 2003. The following year, 2004, the pea/oat crop was excluded and instead field bean and spring wheat was cultivated in three different mixed ratios (field bean/spring wheat; 100:0, 70:30, 30:70). Every year the crops were harvested at four different development stages and the green forages were used in ensiling experiments. In 2005, two feeding experiments, in dairy cows, were carried out at Röbäcksdalen. In experiment I, the cows were fed three different silages; grass silage, grass silage and field bean/spring wheat whole-crop silage (70 % respective 30 % on a dry matter basis) and grass silage and field bean/spring wheat whole-crop silage (30/70) in a change over design. By the end of the experiment all cows had been fed all the silages sometime during the study. In experiment II, the cows were fed grass silage or field bean/spring wheat whole-crop silage together with a low or a high amount of concentrate. During the experiment the cows were fed with the same silage and concentrate until the end of the study. Considering the DM yield in the field experiments the field bean/spring wheat crop should be harvested when the pods are full sized and in the pod fill stage (development stage 79 according to Zadoks et al. [1974]). The field bean/spring wheat crop was easy to ensile and all silos gave a silage quality that were good to medium good. The feeding value, expressed as VOS and concentration of crude protein, were only negligibly affected by harvest time all three years. The results in feeding ...